Nutrient content of banana peel candy to reduce blood pressure in patients with mild hypertension - Marianawati Saragih; Dewi Aryanti; Eva Dewi Rosmawati Purba; Emilia Emilia (Malahayati International Journal of Nursing and Health Science, 2024)
Background: Banana peels are waste from abundant bananas, rich in nutrients and still rarely used. Banana peels contain quite high levels of nutrients, especially vitamins and minerals such as water, fiber, carbohydrates, protein, fat, potassium, calcium, phosphorus, iron, vitamin B and vitamin C. Banana peels can be used to make soft candy. Nutrient content of soft candy from Ambon banana peel to reduce blood pressure in patient with hypertention is arranged. Purpose: To analyze the nutrient content of banana peel candy to reduce blood pressure in patients with mild hypertension. Method: Experimental research with a complete random design. The treatment is to make soft candy from ambon banana peels with the addition of gelatin. In this study, a group Random design was used with three one-time repeats so that there were three experimental units (25 gr; 37,5 gr; 50 gr). The product, soft candy, is tested by 25 trained panelists for hedonic rating test. After that, the product was analyzed by proximat analysis method to find the nutrient content. Results: The nutritional content of soft candy banana peel products were total energy 126.49 kcal, carbohydrates 21.49%, protein 9.16% and fat 0.25%. For mineral nutrients, the highest content was sodium at 61.25 mg, phosphorus at 59.53 mg, potassium 27.3 mg, calcium 15.94 and magnesium 3.5 mg. Determining the formula in the organoleptic test was found to be the best, namely sample 3 was the selected formula seen from the fairly high attribute values ​​in the sensory test of taste, color and aroma. Conclusion: The nutritional content showed that this soft candy could not fullfill the daily requirements for these minerals, each of which was recommended per day. However, it was important to consume other foods that were rich in potassium, calcium and magnesium.